Pengaruh Brand Image dan Service Performance terhadap E-WOM di TripAdvisor InterContinental Bali Sanur Resort - Vera Catur Riliasti; Ni Nyoman Teristiyani Winaya; I Komang Mahayana Putra (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the partial and simultaneous effects of Brand Image and Service Performance on Electronic Word of Mouth (E-WOM) on the TripAdvisor platform at InterContinental Bali Sanur Resort. The research method used is quantitative with an associative approach. Sampling was conducted using a purposive sampling technique with a total of 97 respondents who were guests who had stayed and provided reviews on the TripAdvisor platform. The data analysis technique used multiple linear regression analysis processed through the SPSS 27 program. The partial results of the study show that the Brand Image variable has a positive and significant effect on E-WOM, driven by the main indicator of pride in a positive brand image (Brand Favorability). The Service Performance variable is also proven to have a positive and significant partial effect on E-WOM, driven by the high responsiveness of staff in handling guest needs. Simultaneously, both independent variables significantly affect the accumulation of E-WOM on the TripAdvisor platform. The practical implication for hotel management is the need to optimize unique local identity (Brand Uniqueness) and utilize the newly renovated lobby facilities and beachfront afternoon tea lounge as physical instruments to drive positive reviews in order to boost the hotel's digital popularity ranking.